2020
DOI: 10.31235/osf.io/dh42z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

False beliefs can bootstrap cooperative communities through social norms

Abstract: Building cooperative communities has always been a crucial problem for human societies. Much research suggests that cooperation is facilitated by knowing who exactly is a cooperator and defector, and being able to respond accordingly. As such, anonymous games is thought to hinder cooperation. Here, we show that this conclusion is altered dramatically in the presence of conditional cooperation norms and heterogeneous beliefs about others' behaviours. Specifically, we show that inaccurate beliefs about other pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As the number of infectious individuals increases, the best response function shifts, which can shift equilibrium behaviour from a state where only a few individuals adopt the NPI to a bistable system where most people will either adopt the NPI or not, depending on what they believe others do, and then to a state where almost all engage in the behaviour. Such phenomena have been previously explored in the formation and dynamics of social groups (Morsky and Akçay, 2021). Figures 1b and 1c depict such shifts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the number of infectious individuals increases, the best response function shifts, which can shift equilibrium behaviour from a state where only a few individuals adopt the NPI to a bistable system where most people will either adopt the NPI or not, depending on what they believe others do, and then to a state where almost all engage in the behaviour. Such phenomena have been previously explored in the formation and dynamics of social groups (Morsky and Akçay, 2021). Figures 1b and 1c depict such shifts.…”
Section: Resultsmentioning
confidence: 99%
“…Though we explored the case with small positive or negative biases in these beliefs and found no large impact on the qualitative results (Appendix C), further exploration of the role of inaccurate beliefs in this model could be useful. In a previous compartmental model of norm adoption, it was found that such inaccurate beliefs about population behavior could substantially impact the emergence of a social norm (Morsky and Akçay, 2021). In the context of NPIs, biases in beliefs about population behavior can arise through visibility or salience bias (Han et al, 2019): for instance, people going out dining are more visible than people staying in, which can induce lower perception of NPI behaviors, and delay the onset of NPI adoption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation